Childhood post-transplant lymphoproliferative disorder. Issue 3 (March 2021) - Srivatsa, Kavitha; Taj, Mary
Abstract: Post-transplant lymphoproliferative disorders (PTLDs) are a heterogeneous group of neoplasms that occur as a serious complication of haematopoetic stem cell or solid organ transplantation. They are Epstein Barr virus (EBV) driven in over 90% of the cases. Incidence of PTLD varies from 1 to 20 % depending on the organ transplanted, the intensity of immunosuppression and the recipient's pre transplant EBV status. The pathology of PTLD varies from polymorphic to monomorphic/monoclonal disease which is indistinguishable from a high-grade lymphoma. The clinical course varies from indolent to rapidly progressive, fulminant disease. Over two thirds to 90% of PTLDs are of B cell origin. The current standard of treatment involves reduction of immunosuppressive drugs and if that is not sufficient, use of anti CD20 monoclonal antibody (Rituximab) alone or in combination with conventional chemotherapy. This review offers an overview for healthcare professionals looking after children and young people who may be at risk of or have PTLD. It discusses the pathophysiology, the risk factors, classification and diagnosis of PTLD. It also summarises the current approach to management and monitoring strategies.